Computational advances for and from Bayesian analysis - Andrieu, C; Doucet, A; Robert, C (2004)
The emergence in the past years of Bayesian analysis in many methodological and applied fields as the solution to the modeling of complex problems cannot be dissociated from major changes in its computational implementation. We show in this review how the advances in Bayesian analysis and statistical computation are intermingled.